Efektivitas Aplikasi Fungi Mikoriza Arbuskula dan Arang Hayati terhadap Pertumbuhan Benih Kakao - Dewi Nur Rokhmah; Iing Sobari; Kurnia Dewi Sasmita (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Seedling is an important process in preparing cocoa plant material. The growing medium must have sufficient nutrition and physical properties to enable cocoa seeds to grow well. Arbuscular mycorrhizae fungi (AMF) and biological charcoal (biochar) added into growing media were expected to increase the growth of cocoa seeds. The study aimed to determine the effect of AMF and biological charcoal on the growth of cocoa seeds. The randomized complete block design (RBD) in factorial 2 factors with three replications was used in this study. The first factor was AMF application consisted of two levels, namely: M0 = without AMF and M1 = application of 10 g/seedling AMF (100 spores/seedling). The second factor was the biochar application consisted of 5 factors namely: B0 = no biochar, B1 = 2% rice husk biochar, B2 = 4% rice husk biochar, B3 = 2% albizia wood biochar, and B4 = 4% albizia wood biochar. The variables observed were the height of seedling, number of leaves and stem diameter at 3, 4, 5 and 6 month after planting (MAP), leaf chlorophyll content, weight of dry cocoa seedling, and nutrient content in seedling media. The result showed that the application of AMF significantly affected the height of seedling at 3, 4, 5 and 6 MAP. While the application of biochar significantly affected the height and number of leaves of cacao seedlings.